PERJANJIAN JUAL BELI TENAGA LISTRIK PRA BAYAR ANTARA PELANGGAN DENGAN PT. PLN AREA PEKANBARU (PERSERO) RAYON PANAM - Cia, Rusdah; Hanifah, Mardalena; Hasanah, Ulfia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Electric power services being developed by PT. PLN (Persero) is currently the prepaidservices of electric power, the customers who use electric power prepaid services both newcustomers and migrated customers from electricity users postpaid to prepaid electricity usershave to register first to the nearest PLN office or to the official website of PLN. After registering,there will be an agreement between PLN with the customers to conduct the electricity purchase.However in fact, not all of the pre-paid electricity uses the purchase agreement, for examplethere are some customers who are late for 2-3 months late in paying accounts, and there is thetermination and replacement of electricity postpaid to prepaid electricity unilaterally performedby PLN without any notice and agreement first. Data collection technique used in this research isinterviews, questionnaires, and library research. The research findings concluded are: first, thepurchase agreements between customers and PT. Pekanbaru Area PLN (Persero) Rayon Panamis not purely a legal agreement because the process of installation of pre-paid electricity is donewithout notice and consent from the customer. Second, the effect of purchase agreement pre-paidbetween the customers and PT. Pekanbaru Area PLN (Persero) Rayon Panam is there is theobligation of the customer which is not fulfilled. It is by not paying the electric bill each monthwithin a predetermined time up to 2-3 months in a row causes the electrical disconnection by thePLN as a sanction, but by not paying the electricity bill for 2-3 months, it does not mean thatPLN electricity can replace it by electricity prepaid without the permission from PLN. The writersuggests that, First, PLN should give notice for the termination to the customers in order to avoidmake customers feeling disadvantaged, and for the installation of pre-paid electricity, thecustomer should have the agreement letter. Secondly, as the electricity users, customers shouldrealize for their rights and obligations, the PLN should give prior notice to the customer beforeperforming the electrical disconnection.Keywords: Sale Purchase Agreement - Pre-Paid Electricity - PT. Pekanbaru Area PLN(Persero) Rayon Panam.